Proliferation and differentiation potential of human adipose-derived stem cells grown on chitosan hydrogel. - Tanya Debnath; Sutapa Ghosh; Usha Shalini Potlapuvu; Lakshmi Kona; Suguna Ratnakar Kamaraju; Suprabhat Sarkar; Sumanlatha Gaddam; Lakshmi Kiran Chelluri (PLoS ONE, 2015)
Applied tissue engineering in regenerative medicine warrants our enhanced understanding of the biomaterials and its function. The aim of this study was to evaluate the proliferation and differentiation potential of human adipose-derived stem cells (hADSCs) grown on chitosan hydrogel. The stability of this hydrogel is pH-dependent and its swelling property is pivotal in providing a favorable matrix for cell growth. The study utilized an economical method of cross linking the chitosan with 0.5% glutaraldehyde. Following the isolation of hADSCs from omentum tissue, these cells were cultured and characterized on chitosan hydrogel. Subsequent assays that were performed included JC-1 staining for the mitochondrial integrity as a surrogate marker for viability, cell proliferation and growth kinetics by MTT assay, lineage specific differentiation under two-dimensional culture conditions. Confocal imaging, scanning electron microscopy (SEM), and flow cytometry were used to evaluate these assays. The study revealed that chitosan hydrogel promotes cell proliferation coupled with > 90% cell viability. Cytotoxicity assays demonstrated safety profile. Furthermore, glutaraldehyde cross linked chitosan showed < 5% cytotoxicity, thus serving as a scaffold and facilitating the expansion and differentiation of hADSCs across endoderm, ectoderm and mesoderm lineages. Additional functionalities can be added to this hydrogel, particularly those that regulate stem cell fate.